Tailored dose baclofen in patients with alcoholic liver disease: A case series with 2-year follow-up of hospitalisation. (27th November 2015) - Heydtmann, Mathis; Macdonald, Benn; Lewsey, James; Masson, Neil; Cunningham, Leona; Irnazarow, Aleksandra; Nardone, Amanda; Cosgrave, Jan; Chick, Jonathan
Abstract: Introduction : Alcohol addiction is a major health burden with its consequences including liver disease and frequent hospitalisations. We used tailored-dose baclofen in patients with alcoholic liver disease and investigated hospital re-admissions before and after baclofen dose was initiated as well as tolerability and patient-reported alcohol consumption. Methods : Fifty-three hospitalised patients with alcoholic liver disease started tailored dose baclofen (median: 5.05 months, median highest dose before tapering down: 60 mg). Patients were followed-up for hospitalisation data from the health board database (mean hospitalisation follow up: 31 months) and patients were sent standardized questionnaires. Results : Baclofen was generally well tolerated with dose reductions in four patients. In the 2 years after initiation of the treatment, patients spent on an average of 19.1 d in the hospital per year compared to 25.48 d before the treatment initiation ( p = 0.59). Respondents (19 patients) reported a reduction in alcohol consumption by an average of 58.7% (240.1 g to 144.09 g). Conclusions : After initiation of the baclofen treatment, there was a trend towards decrease in hospitalisations and in patients who answered the questionnaire, alcohol consumption decreased.